Retrospective study of biopsied oral and maxillofacial lesions in pediatric patients from Southern Taiwan - Frank Lei; Jing-Yi Chen; Li-Min Lin; Wen-Chen Wang; Hsieng-Cheng Huang; Chia-Hui Chen; Kun-Yen Ho; Yuk-Kwan Chen (Elsevier, 2014)
Background/purpose: This study aimed to provide updated information on biopsied oral and maxillofacial (OMF) pediatric lesions in Southern Taiwan. The data were compared with our previous study (1985-1996) and also with previous studies from Northern Taiwan and other countries. Materials and methods: Biopsied cases from a pediatric population (0-15 years old), between 1997 and 2011, were retrieved from the Oral Pathology Department of our institution. Age, sex, location, and histological diagnoses were recorded. The data were divided into three age levels: 0-5 years, 6-10 years, and 11-15 years. The OMF lesions were classified into four categories: tumor/tumor-like lesions, cystic/pseudocystic lesions, inflammation/reactive lesions and other miscellaneous lesions. Results: Of a total of 36,264 biopsied cases, 1023 OMF biopsies were recorded for patients between 0 and 15 years. Most lesions were in the inflammation/reactive group (n = 451), followed by the groups of tumor/tumor-like lesions (n = 240), cystic/pseudocystic lesions (n = 196) and other miscellaneous lesions (n = 136). Most cases were located in the 11-15 year age group. Mucocele was the most common lesion, followed by odontoma and dentigerous cyst, which comprised 41.5% of total numbers of pediatric biopsied lesions. Conclusion: There was an increase of 52% of biopsied pediatric OMF lesions in the current series (1997-2011) as compared to our previous study (1985-1996). The present study showed a similar trend to our previous study, the study from Northern Taiwan and also other studies. However, some detailed information was different, perhaps due to the different criteria and different time range and population.